Treasured Oases A Selection of Jao Tsung-i's Dunhuang Studies - Jao, Tsung-i (Brill, 2022)
Dunhuang: China's traditional northwest frontier and overland conduit of exchange with the Old World. Jao Tsung-i: China's last great traditional man of letters, polymath, and pioneer of comparative humanistic inquiry during Hong Kong's global heyday. Jao and Dunhuang had a special relationship that this book makes accessible in English for the first time. Inside, Jao proposes an entirely new school of Chinese landscape painting, reconsiders Dunhuang's oldest manuscripts as its newest research field, and explores topics ranging from comparative religion to medieval multimedia.